Market Structure, Product Differentiation, and Industrial Research - Comanor, William S. (Quarterly Journal of Economics, 1967)
Research and firm size within industries, 640. — Research elasticities and average firm size, 644. — Market structure and the level of research, 645. — The role of technical entry barriers, 652. — Conclusions, 656.